Advanced Technologies in Hydropower Flow Systems - Adamkowski, Adam; Bergant, Anton (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Hydropower is an essential part of the renewable energy sector. High efficiency, immediate availability, and safe operation of hydroelectric power plants are the three key issues in recent developments in the hydropower sector. This book brings together the latest achievements addressing these key factors. In addition, one contribution deals with the alternative harvesting of hydro energy from pivoted cylinders by generating flow-induced vibrations, which are unwanted phenomena in classical pump-turbine units.